Evaluation of mestizos and use of multivariate techniques to identify outstanding corn lines - Sánchez-Ramírez, Francisco Javier; Mendoza-Castillo, Ma. del Carmen; Mendoza-Mendoza, Carmen Gabriela (Revista Mexicana de Ciencias Agrícolas, 2020)
It is common for plant breeding programs based on hybridization schemes to start with hundreds of inbred lines; the foregoing makes discrimination essential to continue with desirable attributes. This work was carried out in 2017 at the Graduate College and the Superior Technological Institute of the West of the State of Hidalgo, to choose outstanding mestizos, which were formed with 34 lines (S3-S4) developed for the production of grain in conditions of limited or temporary irrigation, these were identified by integral phenotypic selection, principal component analysis and graphical dispersion analysis. High performance criteria and agronomic-morphological characteristics of interest for grain production and for its improvement were applied. The analysis of main components and the analysis of graphic dispersion contributed to a reliable characterization and easy graphic visualization of the phenotypic expression of the mestizos. The outstanding lines were those that gave rise to the mestizos identified as ^1, ^4, ^5, ^8, ^10, ^11, ^14, ^16, ^19 and ^27, which yielded between 8.5 and 6.2 t ha-1. They also had high values of ear weight, diameter and length of ear, and grain weight; the mestizo ^27 also stood out for its prolificity.
Keywords: graphical dispersion analysis; High Valleys of Central Mexico; line x tester; principal component analysis